Pedagogical Concerns Regarding School History - Gandhi, Malli (JOURNAL OF INDIAN EDUCATION, 2015)
History has been an important component of school curriculum for a long time. Since Independence a number of changes have taken place both in the content and teaching of history. In more recent years, there have been changes in almost all the aspects of history namely, its concept, approach and also in the methodology of teaching. The main reason for this change is the deeper understanding that developed about the purpose of studying history. However, unfortunately, these changes have not been reflected in the textbooks and pedagogical issues of teaching and learning history, particularly in schools. New findings brought out enormous research, with the aid of advanced tools that is being carried out in the universities and advanced centres of learning, have not been reflected in the classroom practices and school text books. The old themes with emphasis on chronological approach dealing with the dynastic changes and biographical details, presented in a narrative style are being continued both in classrooms and textbooks. This is more deplorable to say the least. For, the scope of history has broadened as it includes now, within its purview, every aspect of life of human beings in society from the time of the evolution of man on earth about a million years ago. Also, the purpose of studying history has changed enormously. Therefore, there is a need to bring innovative approaches in the pedagogical aspects at school level. The aims and objectives of the paper is to suggest the teachers of history to be aware of new methods and techniques of teaching learning History at school level, to adopt new pedagogical approaches such as constructivist approach in making history teaching effective in the classrooms, help them adopt a constructivist approach in the classroom activities, learning process, and able to organise activities, discussions, within the parameters of constructivism in history classroom.